Craving alterreal authenticity through the post-postmodern lens: An experimental inquiry. (February 2023) - Wong, IpKin Anthony; Sun, Danni; Xiong, Xiling; Li, Xi
Abstract: This research takes a post-postmodern stance to investigate tourists' predisposition toward alterreal authenticity (i.e., altered reality). It draws on Schachter's two-factor theory of emotion to highlight a model that examines the effects of authenticity and cultural difference, and their interactions on cultural-heritage consumption, through a field experiment. Results point to a two-step mechanism in authenticity negotiation in which psychological arousal is diffused through exposure to authenticity stimuli followed by cognition of the arousal situation conditioned upon tourist cultural background. This research not only heeds the call from the literature to enrich the methodological silos in authenticity discourse through causal inferences; it also provides early empirics to the post-postmodern view of authenticity, which conjectures means for tourists to imaginatively authenticate their experiences.